(untitled) (Ameghiniana, 2013)
The presence of the genus Zygograptus in the lower levels of the Gualcamayo Formation is indicated and details of its morphology are described. The genus is associated to Glyptograptus austrodentatus Harris & Keble and Paraglossograptus etheridgei (Harris ). The age of the Gualcamayo Formation is placed in the early Llanvirnian.